2020s Heroes Are Not Fearless: The Impact of the COVID-19 Pandemic on Wellbeing and Emotions of Italian Health Care Workers During Italy Phase 1 - Marton, Giulia; Vergani, Laura; Mazzocco, Ketti; Garassino, Marina Chiara; Pravettoni, Gabriella (Frontiers in Psychology, 2020)
Objective: The aim of the study was to investigate mental health and emotional status of physicians working during phase 1 of the COVID - 19 pandemic in Italy. Methods: A total of 458 Italian Health Care Workers working during phases 1 of the COVID-19 outbreak were voluntarily enlisted in the study and recruited with the snow-ball technique. We examined our variables with the General Health Questionnaire - 12 and with Visual Analogue Scales. Results: The sample has a high level of psychological distress, the emotional status was characterized by high level of fear for family members and cohabitants and for patients. Perceived control, fear for patients and for family members and cohabitants, feeling alone and anger all contribute in a decreased mental health in Italian physicians. Conclusions: Italian Health Care Workers’ mental health and emotional status have to be considered to prevent high risk of burnout and PTSD. It becomes pivotal, in the next months to implement tailored psychological intervention to take care for Health Care Workers and to prevent costly consequences for them, patients and the healthcare system.